THE INTREPRETATION OF A WORD OR POETRY IN MATNAZAR ABDULHAKIM’S JOURNALISM (American Journal of Interdisciplinary Research and Development, 2022)
In this article are highlighted journalistic views about literary words and poetry in the literary thoughts janre of well-known poet M. Abdulhakim